Analysis of Heat Dissipation Performance between a Horizontal and Longitudinal Battery Pack Based on Forced Air Cooling. Issue 7 (13th September 2016) - Jiang, Fuping; Xu, Xiaoming; Hu, Donghai
Abstract: A battery pack is the main energy storage element, and directly affects the performance of an electric vehicle. Battery thermal management system research and its development for a modern electric vehicle is required. This paper selects the forced air cooling of battery pack as the research object, and uses simulation methods to research the heat dissipation performance with different structures of battery packs. The results indicate that according to the four types of transient state conditions, the rising temperature of both battery packs are significantly higher than the temperature difference, the maximum temperature rise and temperature difference of a horizontal battery pack are lower than a longitudinal battery pack. When an electric vehicle begins to decrease speed, the curves of temperature rising and temperature difference increase. This shows the internal heat is continuously rising, so even in a electric vehicle beginning to decrease speed, the fan must work. The reference basis for choosing battery pack type and an analysis of heat flow field characteristics, including fan run‐time control, are offered.